Decipher manifestations and Treg /Th17 imbalance in multi-staging rheumatoid arthritis and correlation with TSDR/RORC methylation. (November 2020) - Huang, Yao; Wang, Hui; Ba, Xin; Chen, Zhe; Wang, Yu; Qin, Kai; Huang, Ying; Shen, Pan; Tu, Shenghao
Graphical abstract: Highlights: Rheumatoid arthritis (RA) in different staging possessed diverse manifestations. Treg/Th17 imbalance varied with disease staging. Early active RA exhibited aberrant DNA methylation. Treg/Th17 imbalance might integrate with FOXP3 TSDR/RORC methylation result in the development of RA. Abstract: T regulatory (Treg)/T-helper (Th) 17 imbalance has been shown to integrate with epigenetics to result in the development of autoimmune diseases. We aim to investigate the influence of disease staging on Treg/Th17 cells and whether the aberrant DNA methylation is implicated in the development of rheumatoid arthritis (RA). By recruiting 65 patients with multi-staging RA and 20 healthy controls (HC), we found that patients with active RA exhibited relative lymphopenia and higher WBC, neutrophils, and PLT. Circulating Treg/Th17 in patients with early active RA was significantly decreased. The expression of IL-6 and IL-17A was significantly increased in early active RA, whereas that of IL-10 and TGF-β was on the contrary. Furthermore, the frequency of Treg cells and Treg/Th17 were negatively correlated with DAS28, and the frequency of Th17 cells was on the contrary. Levels of DNA methylation related enzymes had significant difference between early active RA and HC. Relative hypermethylation was observed at the gene level for Treg-specific demethylated region (TSDR) and hypomethylation for retinoic acid‐related orphan receptor (ROR)-C in early active RA. Thus, manifestations of RA and Treg/Th17 imbalance vary with disease staging, and the aberrant DNA methylation pattern may contribute to RA disease pathogenesis. Our results highlight the importance of disease staging in clinical research.